DIGITAL RIGHTS: LATIN AMERICA AND THE CARIBBEAN - MAGRANI, EDUARDO (RIO DE JANEIRO FGV-DIREITO, 2017)
The Internet is a decentralized global network that makes communication, information and learning easier. Basic democratic practices, such as discussing matters of public interest and participating in the political process, will be increasingly related to the digital world. This publication presents an overview of the most relevant issues in the area of Digital Law in Latin American countries, as a result of the Project 'Digital Rights: Latin America and the Caribbean', an International Newsletter coordinated in Brazil by Professor and Researcher of FGV, Eduardo Magrani. The project emerged in 2012 as an initiative of leading Latin American think tanks working on issues related to Internet regulation and governance interested in consolidating human rights in the digital world. The regulation of net neutrality, the regulation of copyright and the responsibility of intermediaries, restrictions on freedom of expression by electronic means and data protection policies are some of the themes that can be found in this work of selected articles. Being informed about these subjects is a fundamental requirement for promoting dialogue and consensus around these issues. This publication is intended to be a useful tool for a broad community of stakeholders interested in the Digital Law landscape in Latin America.
INGLÊS
Inclui bibliografia.
Keywords: INTERNET; MOVIMENTOS SOCIAIS; DIREITOS HUMANOS; LIBERDADE DE EXPRESSAO; PROTECAO DE DADOS; DIREITOS AUTORAIS; CRIME POR COMPUTADOR; GERAL; LIVRO ELETRONICO / EBOOK